2019
DOI: 10.1155/2019/2831969
|View full text |Cite
|
Sign up to set email alerts
|

Canadians’ Dietary Intake from 2007 to 2011 and across Different Sociodemographic/Lifestyle Factors Using the Canadian Health Measures Survey Cycles 1 and 2

Abstract: Background. Nutrition is an important factor that impacts health, yet in Canada, there have been only a few surveys reflecting dietary intakes. The Canadian Health Measures Survey (CHMS) is a national survey that includes both food intake data as targeted questions and objective health measures. The aim of this research was to determine how food group intake data reported in CHMS is related to food group intakes from Canadian Community Health Survey (CCHS) (2004). A secondary objective was to examine the dieta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
1
5
0
Order By: Relevance
“…Among supplement users, total vitamin D intake and vitamin D status were not different between our ethnic groups, and serum 25OHD was on average above 50 nmol/L. In the present study, the main source of dietary vitamin D was from vitamin D fortified milk with dietary vitamin D intakes consistent with national surveillance datasets (Hosseini et al 2019). Even though the 30-d FFQ used in our study prevents direct comparison to the EAR, it is notable that the 75 th percentile of dietary intakes in South Asian group was below the EAR.…”
Section: Resultssupporting
confidence: 69%
“…Among supplement users, total vitamin D intake and vitamin D status were not different between our ethnic groups, and serum 25OHD was on average above 50 nmol/L. In the present study, the main source of dietary vitamin D was from vitamin D fortified milk with dietary vitamin D intakes consistent with national surveillance datasets (Hosseini et al 2019). Even though the 30-d FFQ used in our study prevents direct comparison to the EAR, it is notable that the 75 th percentile of dietary intakes in South Asian group was below the EAR.…”
Section: Resultssupporting
confidence: 69%
“…FBS data are also limited by the fact that they do not take into account food and nutrient losses that may occur as a result of processing, spoilage, trimming or waste [3]. To overcome these limitations, numerous countries resorted to individual nutrition surveys for the examination of dietary shifts and food consumption trends at the population level [4,5,6,7]. In contrast to FBSs, data from individual surveys more closely reflect actual food consumption and provide information not only on the average intake levels, but also on their distribution across various groups within the population [3].…”
Section: Introductionmentioning
confidence: 99%
“…A limitation of our study was the food frequency questionnaire used in the analysis, which does not include a few foods from grains and meat and alternatives groups [ 19 ]. Furthermore, our study is a cross-sectional study; thus, causality cannot be concluded, and there are chances of reverse causality due to the nature of cross-sectional studies.…”
Section: Discussionmentioning
confidence: 99%
“…We used the usual dietary intake data collected using a food frequency questionnaire through the CHMS household questionnaire [ 14 , 15 , 19 ]. This food frequency questionnaire was used to collect usual daily dietary intake.…”
Section: Methodsmentioning
confidence: 99%